2013
DOI: 10.1212/01.wnl.0000435556.21319.e4
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-first and neurodegeneration-first profiles characterize incident amyloid PET positivity

Abstract: Objective: To estimate the incidence of and to characterize cognitive and imaging findings associated with incident amyloid PET positivity.Methods: Cognitively normal (CN) participants in the Mayo Clinic Study of Aging who had 2 or more serial imaging assessments, which included amyloid PET, FDG-PET, and MRI at each time point, were eligible for analysis (n 5 207). Twelve subjects with Alzheimer disease dementia were included for comparison.Results: Of the 123 CN participants who were amyloid-negative at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
137
1
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(155 citation statements)
references
References 40 publications
16
137
1
1
Order By: Relevance
“…Twenty-nine percent of the MCI cases from the Mayo Clinic Aging Study and 17% from the Alzheimer's Disease Neuroimaging Initiative had neurodegeneration (by MRI or [ 18 F]-fluorodeoxyglucose-PET) without amyloid deposition, 31 and 42% of the Mayo Clinic Aging Study subjects who became amyloid-positive at follow-up had evidence of neurodegeneration before showing amyloid positivity. 32 WMLs, as markers of small vessel disease, are independent predictors of dementia. 15 Some studies found that WMLs were better predictors of dementia than hippocampal volume, 16 and others showed that WMLs were associated with increased Ab deposition in subjects with AD.…”
Section: Resultsmentioning
confidence: 95%
“…Twenty-nine percent of the MCI cases from the Mayo Clinic Aging Study and 17% from the Alzheimer's Disease Neuroimaging Initiative had neurodegeneration (by MRI or [ 18 F]-fluorodeoxyglucose-PET) without amyloid deposition, 31 and 42% of the Mayo Clinic Aging Study subjects who became amyloid-positive at follow-up had evidence of neurodegeneration before showing amyloid positivity. 32 WMLs, as markers of small vessel disease, are independent predictors of dementia. 15 Some studies found that WMLs were better predictors of dementia than hippocampal volume, 16 and others showed that WMLs were associated with increased Ab deposition in subjects with AD.…”
Section: Resultsmentioning
confidence: 95%
“…[2][3][4] However, the pathophysiologic correlates of Ab-independent atrophy remain unclear. Our work shows that AD-like neurodegeneration (i.e., AD signature cortical thinning) has a direct relationship with abnormal biomarker of tau pathology.…”
Section: Associations Of Ad Signature Cortical Thicknessmentioning
confidence: 99%
“…1 However, recent work has observed that some cognitively normal (CN) individuals have neurodegeneration (e.g., AD-like brain atrophy on structural MRI) independent of amyloidosis. [2][3][4] These observations motivate the investigation of tau-related neurodegenerative process in preclinical AD. In addition, discrepant data exist regarding the relationships between amyloidosis or neurodegeneration and cognitive decline in preclinical AD.…”
mentioning
confidence: 93%
“…Demonstration that SDS-soluble Aβ measured by immunoassay was better than post mortem PiB binding has important implications for imaging-based biomarkers [66]. In some PiB-negative cases, a combination of pre-existent non-AD pathology and tau-mediated neurodegeneration may be present prior to Aβ pathology [67].…”
Section: Introductionmentioning
confidence: 99%
“…Demonstration that SDS-soluble Aβ measured by immunoassay was better than post mortem PiB binding has important implications for imaging-based biomarkers [66]. In some PiB-negative cases, a combination of pre-existent non-AD pathology and tau-mediated neurodegeneration may be present prior to Aβ pathology [67].Hippocampal atrophy in the elderly, demonstrated by modern imaging methods and confirmed by postmortem diagnosis of AD [44,68], has been shown to be an important and under-appreciated brain lesion of aging [69].A review of 2,861 neurodegenerative disease cases of the National Alzheimer's Coordinating Center Registry (NACCR) showed high diagnostic accuracy for AD (85% sensitivity, 51.1% specificity) and low sensitivity for DLB (32% for pure AD and 12% for AD+DLB) with a specificity over 58% [70]. Evaluation of the accuracy of current clinical diagnostic methods for AD in 919 autopsy cases from the database of the NACC (2005-2010) revealed a sensitivity from 70.9 to 87.3% and a specificity of 44.3 to 70.8%.…”
mentioning
confidence: 99%